การนำสื่อมัลติมีเดียมาช่วยสอนภาษาอังกฤษในโรงเรียน - อินธิราช, พินิจ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด, 2024)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อส่งเสริมการเรียนรู้คำศัพท์ภาษาอังกฤษของนักเรียน  2) เพื่อเปรียบเทียบผลสัมฤทธิ์การเรียนรู้คำศัพท์ภาษาอังกฤษก่อนและหลังการใช้สื่อมัลติมีเดียของนักเรียน 3) เพื่อศึกษาความพึงพอใจของนักเรียนชั้นมัธยมศึกษาที่มีต่อการใช้สื่อมัลติมีเดียการเรียนรู้คำศัพท์ภาษาอังกฤษ กลุ่มตัวอย่างที่ใช้ในการวิจัย ได้แก่ นักเรียนโรงเรียนดอนแคนดอนหวายสามัคคี จำนวน 20 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ การเรียนรู้คำศัพท์ก่อนเรียนและหลังเรียน โดยใช้สื่อมัลติมีเดีย สถิติที่ใช้ในการวิจัย ได้แก่ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน และ t-test             ผลการวิจัยพบว่า 1. นักเรียนมีความกระตือรือร้นอยากที่จะเรียนคำศัพท์ใหม่ๆ 2. นักเรียนเรียนรู้คำศัพท์ภาษาอังกฤษระหว่างก่อนเรียนและหลังเรียนของนักเรียนโรงเรียนดอนแคนดอนหวายสามัคคี มีผลรวมคะแนนการทดสอบก่อนเรียนได้เท่ากับ 7.16 คะแนน และผลรวมคะแนน การทดสอบหลังเรียนเท่ากับ 20 คะแนน ค่าดัชนีประสิทธิผล (E.I) ได้เท่ากับ 0.5426 หรือคิดเป็น ร้อยละ 54.26 แสดงว่านักเรียนมีความรู้เพิ่มขึ้น 3. นักเรียนมีความพึงพอใจต่อการเรียนรู้คำศัพท์ใหม่ๆ ในภาพรวมอยู่ในระดับมากสุด เนื้อหาในสื่อมัลติมีเดียเข้าใจง่าย อักษร รูปภาพเคลื่อนไหว  ทำให้เกิดความเร้าใจอยากที่จะเรียน สื่อมัลติมีเดียมีความน่าสนใจ มีเสียงพูด รูปภาพเคลื่อนไหวและเสียงดนตรีประกอบ ทำให้นักเรียนเกิดความต้องการอยากเรียนรู้ มีความพึงพอใจโดยรวมในระดับมากทีสุด              The objectives of the research article were 1) to promote students' learning of English vocabulary. 2) to compare students’ learning achievement of English vocabulary learning before and after by using multimedia, and 3) to study satisfaction of students towards the use of multimedia for English. A sample group was mathayom 2 students totally 20 students in Donkean Donwai school. The study instruments were used three lesson plans concerning English vocabulary learning by using multimedia, English vocabulary achievement. The statistics used were frequency, percentage, mean, standard deviation and t-test.             The findings were as follows: 1. students were actived to learn new words.  2. The pre-test 7.16 points and post test 14 points. Effectiveness index of using multimedia for English vocabulary learning enhancement in Mathayomsuksa 2 students was 0.5426, showing that the students’ English vocabulary learning by using multimedia increased 54.26%. 3. The students are satisfied with learning new vocabulary. Overall, it is at the highest level. The content in multimedia is easy to understand, with letters and moving pictures. Makes you excited and want to study. Multimedia is interesting, with speech, moving pictures and music. Make students want to learn. Overall satisfaction is at the highest level.